Penyelesaian Numerik Advection Equation 1 Dimensi dengan EFG-DGM - Sadono, Kresno Wikan (Department of Civil Engineering, Diponegoro University, 2016)
Differential equation can be used to model various phenomena in science and engineering. Numerical method is the most common method used in solving DE. Numerical methods that popular today are finite difference method (FDM), finite element method (FEM) dan discontinuous Galerkin method (DGM), which the method includes mesh based. Lately, the developing methods, that are not based on a mesh, which the nodes directly spread in domain, called meshfree or meshless. Element free Galerkin method (EFG), Petrov-Galerkin meshless (MLPG), reproducing kernel particle method (RKPM) and radial basis function (RBF) fall into the category meshless or meshfree. Time integration generally use an explicit Runge Kutta 4th order, Newmark- , HHT- , Wilson- dll. This research was carried out numerical simulations DE, by combining the EFG method to solve the domain space and time integration with DGM methods. EFG using the complete order polynomial 1, and DGM used polynomial order 1. The equation used advection equation in one dimension. EFG-DGM comparison with analytical results also performed. The simulation results show the method EFG-DGM match the one-dimensional advection equations well.